A novel Mg(OH)2 binding layer-based DGT technique for measuring phosphorus in water and sediment. Issue 2 (14th January 2020) - Xie, Fazhi; Li, Lu; Sun, Xiaoyan; Hu, Tingting; Song, Kang; Giesy, John P.; Wang, Qilin
Abstract : Diffusive gradients in thin films (DGT) have gained wide attention for in situ measurement of reactive phosphorus species (PO4 ) in natural water, sediments and potentially soils. Abstract : Diffusive gradients in thin films (DGT) have gained wide attention for in situ measurement of reactive phosphorus species (PO4 ) in natural water, sediments and potentially soils. In this study, a novel Mg(OH)2 binding gel was formed using magnesium hydroxide obtained by in situ hydration of calcined magnesium oxide. Laboratory scale experiments showed that the novel Mg(OH)2 gel had a homogeneous dispersion of fine particles of Mg(OH)2 with a particle size of 2–5 μm. With 10 mL of 2.0 mol L −1 NaOH as the eluting agent, the optimal elution efficiency of PO4 on the Mg(OH)2 gel was 72 ± 5%. There were linear relationships between the accumulated PO4 mass and the applied PO4 concentration (0.1 to 20 mg P per L), time (0 to 24 h) and temperature (22 to 40 °C). The capacity of the Mg(OH)2 binding layer was determined to be 99.5 μg P per disc. Tests in synthetic seawater, Chaohu Lake and Yihai Pond confirmed that Mg(OH)2 -DGT was able to accurately measure phosphorus up to 10 days. This was indicated by the good agreements between the concentrations measured by DGT ( C DGT ) technology and by an ex situ chemical method in solution ( C soln ), with a C DGT / C soln ratio between 0.91 and 1.09.